The effects of extracellular and intracellular Hop on cell migration processes - Contu, Lara (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 2014)
The Hsp70/Hsp90-organising protein (Hop) is a 60 kDa co-chaperone that acts as an adaptor molecule, facilitating the transfer of client proteins between the Hsp70 and Hsp90 chaperone systems. Hop functions both intracellularly and extracellularly and has been implicated in many processes involved in cancer progression, including cell migration and invasion. Little is known about the mechanisms or domains by which extracellular Hop functions. In addition, little is known about the effects of Hop on signalling molecules involved in cell migration and invasion through regulation of actin dynamics. It was hypothesised that both extracellular and intracellular pools of Hop would regulate distinct cell migration processes by activation of cell signalling pathways or direct interactions with signalling intermediates. HS578T cells were treated with recombinant full length and truncated murine Hop proteins (overexpressed and purified in this study) to determine the effects of extracellular Hop and the independent domains on cell migration processes. Additionally, RNA interference (RNAi) techniques were used to determine the effect of Hop knockdown on cell migration related signalling intermediates and cell morphologies. A short hairpin RNA (shRNA) system for the stable knockdown of Hop was developed and used for a number of these studies. Treatment of HS578T cells with the TPR2A2B and TPR1 domains of Hop resulted in a significant decrease in cell migration and caused changes in the actin cytoskeleton and extracellular matrix proteins, gelatin and fibronectin. RhoC immunoprecipitated in a common complex with Hop and Hsp90. Hop knockdown reduced levels of actin and total RhoC, as well as active RhoC. In addition, knockdown of Hop resulted in a reduced migratory phenotype. We interpreted these data to indicate that intracellular Hop played a role in cell migration through regulation of RhoC activity, either through a direct interaction between Hop and RhoC, or an indirect interaction of RhoC with the Hsp90 multichaperone heterocomplex. Taken together, the data suggested that extracellular and intracellular Hop played distinct roles in extracellular and intracellular processes that lead to actin dynamics and cell migration. Understanding the mechanistic role of Hop in these processes is essential as it would aid in assessing the viability of Hop as a potential drug target for the treatment of metastatic cancers.
Keywords: Heat shock proteins; Metastasis; Cancer -- Chemotherapy; Molecular chaperones; Cell migration